Efektivitas Asesmen Diagnostik dalam Pembelajaran Berdiferensiasi pada Pelajaran Bahasa Indonesia - Gusti Ayu Putu Trisna Wulandari Wulandari; Ida Bagus Putrayasa; I Nengah Martha (Nusantara: Jurnal Pendidikan Indonesia, 2023)
Students have very diverse backgrounds, so diagnostic assessments are needed in the practice of learning Indonesian at SMA Negeri 1 Kuta Utara. Diagnostic assessments are divided into two, namely non-cognitive diagnostic assessments and cognitive diagnostic assessments. This study is qualitative descriptive research, namely a research method which has the nature of presenting the reality according to the data obtained with the aim of illustrating how effective diagnostic assessment is in differentiated learning. Diagnostic assessments carried out in differentiated learning in Indonesian Language Lessons at SMA Negeri 1 North Kuta are very effective. After carrying out a diagnostic assessment, teachers can create learning that suits the characteristics, interests and abilities of students, relating to processes, content, products and learning environments. The use of diagnostic assessments can increase students' interest in learning Indonesian, because apart from making it easier to understand the material, learning is also tailored to students' readiness, interests and abilities.